Evaluating Government Policies to Enhance the Quality of Basic Education in Urban Areas - Nathan, Henri; Saputri, Thalia Melda (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2025)
This research evaluates government policies aimed at improving the quality of basic education in urban areas, focusing on their effectiveness and impact on student outcomes. Through a mixed-methods approach, the study analyzes quantitative data from standardized test scores, attendance records, and teacher quality metrics, alongside qualitative insights from stakeholder interviews and focus groups. The findings reveal significant positive correlations between increased funding, professional development for teachers, and enhanced curriculum relevance with improved student performance and engagement. However, the evaluation also highlights persistent challenges, including inequities in resource distribution, high teacher turnover rates, and limited access to technology, which continue to hinder educational equity. The study underscores the need for comprehensive, multifaceted strategies that address systemic barriers and promote equitable educational opportunities for all students. Recommendations include sustained investment in urban education, enhanced support systems for teachers, and strengthened community partnerships. By integrating insights from this evaluation with existing literature, the research contributes to the ongoing discourse on effective educational reform in urban settings, emphasizing the importance of collaborative efforts to create an inclusive and high-quality educational environment for all learners.